2015
DOI: 10.1002/anie.201409877
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Tris(acetylacetonato)iron(III)/(II) Redox Couple in p‐Type Dye‐Sensitized Solar Cells

Abstract: An electrolyte based on the tris(acetylacetonato)iron(III)/(II) redox couple ([Fe(acac)3](0/1-)) was developed for p-type dye-sensitized solar cells (DSSCs). Introduction of a NiO blocking layer on the working electrode and the use of chenodeoxycholic acid in the electrolyte enhanced device performance by improving the photocurrent. Devices containing [Fe(acac)3](0/1-) and a perylene-thiophene-triphenylamine sensitizer (PMI-6T-TPA) have the highest reported short-circuit current (J(SC)=7.65 mA cm(-2)), and ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
196
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(199 citation statements)
references
References 28 publications
3
196
0
Order By: Relevance
“…The D values reported in acetonitrile ranged from 0.56 © 10 ¹5 to 1.5 © 10 ¹5 cm 2 s ¹1 , depending on the electrochemical techniques. 14,15,22,26 The D value of Fe(acac) 3 in BMPTFSA was much smaller than those in acetonitrile, reflecting the higher viscosity (73 mPa s) of BMPTFSA containing 10 mM Fe(acac) 3 . As abovementioned, the negative redox potentials of [Fe(CN) 6 ] 3¹ and Fe(acac) 3 are considered suitable for the anolyte of the redox flow batteries.…”
Section: ¹1mentioning
confidence: 96%
See 1 more Smart Citation
“…The D values reported in acetonitrile ranged from 0.56 © 10 ¹5 to 1.5 © 10 ¹5 cm 2 s ¹1 , depending on the electrochemical techniques. 14,15,22,26 The D value of Fe(acac) 3 in BMPTFSA was much smaller than those in acetonitrile, reflecting the higher viscosity (73 mPa s) of BMPTFSA containing 10 mM Fe(acac) 3 . As abovementioned, the negative redox potentials of [Fe(CN) 6 ] 3¹ and Fe(acac) 3 are considered suitable for the anolyte of the redox flow batteries.…”
Section: ¹1mentioning
confidence: 96%
“…In the electrochemical field, the redox reaction using tris(acetylacetonato)iron complex (Fe(acac) 3 ) has been examined in organic electrolytes and deep eutectic solvents for such applications as redox flow batteries and photoelectrochemical cells. [14][15][16] We have reported that the metal complexes with acac ¹ , such as Pd(acac) 2 and Pt(acac) 2 , are stable in TFSA ¹ -based ionic liquids. [17][18][19] In the present study, the redox properties of Fe(acac) 3 were investigated in BMPTFSA.…”
Section: Introductionmentioning
confidence: 99%
“…Among the metal-oxide materials, Nickel oxide (NiO) is a promising candidate for wide-band gap p-type semiconductors, which is the most common semiconductor employed in the fabrication of p-type DSSCs [4]. However, the reported highest conversion efficiency of p-type DSSCs to date is 2.4 %, the value is still lagging behind the best n-DSSCs' conversion efficiency [5].…”
Section: Introductionmentioning
confidence: 99%
“…The reported highest conversion efficiency of p-type DSSCs to date is 2.4 % (with NiO as a photocathode, PMI-6T-TPA as a sensitizer, and Tris(acetylacetonato)iron(III)/(II) redox couple as a redox mediator) [5]. The poor performance of p-DSSCs is the major obstacle toward the high-efficiency tandem pnDSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…This conspicuous difference of efficiencies between n-and p-type devices appears now as the gap to overcome and the actual limiting factor for the realization of t-DSCs with improved performances in comparison to the DSC with single photoactive electrode [12]. By far, the most important cathodic material for p-DSC is nanostructured NiO [11,12,19,31,[36][37][38][39][40][41] with which p-DSCs have reached a maximum of conversion efficiency of 2.55% when the electrolyte contained an iron-based redox shuttle [42], whereas the precedent record of 1.67% was achieved with a cobalt-based mediator [43]. All p-DSCs achieving more than 1% of overall conversion efficiency have insofar utilized the multifunctional dye PMI-6T-TPA [29] (Figure 8).…”
Section: Cathodic Materials For P-dscsmentioning
confidence: 99%